Development of a Digital Leadership Model for Administrators at Suan Dusit University - Yuangaksorn, Benyapa; Janthon, Ua-aree; Tungdamnernsawad, Supaporn (Mahachula Academic Journal, 2026)
This research aimed to: 1) examine the current state of digital leadership and development needs for digital leadership, and 2) develop a digital leadership model for administrators at Suan Dusit University. This quantitative research included a sample of 385 participants. The questionnaire had a reliability coefficient of 0.981. Data were analyzed using descriptive statistics, exploratory factor analysis, Pearson correlation analysis, and structural equation modeling. The research findings revealed that: 1) the current state of digital leadership was at a high level ( = 4.02, SD = 0.800), while development needs were at the highest level ( = 4.53, SD = 0.648). Human resource development in the digital era showed the highest priority need (PNImodified = 0.58), followed by digital knowledge and skills (PNImodified = 0.54). 2) The digital leadership model for Suan Dusit University administrators consisted of four main components: (1) Strategic Leadership and Digital Vision, explaining 23.961% of the variance; (2) Change Leadership and Digital Culture, explaining 23.115% of the variance; (3) Personnel Development Leadership and Digital Innovation, explaining 18.307% of the variance; and (4) Governance Leadership and Digital Responsibility, explaining 15.040% of the variance. All four components showed very high correlations with each other (r > 0.80, p < .01). The structural equation model demonstrated excellent fit with the empirical data (χ²/df = 1.624, CFI = 0.999, TLI = 0.998, RMSEA = 0.046, SRMR = 0.008).